2022
DOI: 10.1055/a-1753-2634
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Architecture Characters and Changes of Pediatric Moyamoya Disease after Combined Bypass Surgery

Abstract: Objective We aimed to analyze the angioarchitecture characters and changes after combined bypass surgery (CBS) in pediatric moyamoya disease. Methods We retrospectively analyzed our database of consecutive patients with moyamoya angiopathy who received treatment. Only pediatric MMD cases aged between 3 to 19 years old whose pre- and post-operative imaging examinations including digital subtraction angiography and magnetic resonance imaging were enrolled in this study. The main trunk vessels stenosis and the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…On the relationship between surgical treatment and MMD progression, Park et al conducted a retrospective study focusing on pediatric MMD patients treated by indirect revascularization and found that 20 of 34 patients (58.8%) had contralateral progression following surgery, whereas the mean follow-up duration of their cohort was long with 35.3 months (IQR, 18.1-100 months) [25]. Our previous studies have demonstrated that unilateral combined bypass surgery was associated with rapid radiological progression of contralateral vessels at short-term follow-up, resulting in rapid aggravation of main trunk stenosis and decreased cerebral blood ow on the non-OP side [11,13]. In the current study, we identi ed contralateral radiological progression in 11 pediatric patients (40.7%) within 3 to 6 months following unilateral combined bypass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the relationship between surgical treatment and MMD progression, Park et al conducted a retrospective study focusing on pediatric MMD patients treated by indirect revascularization and found that 20 of 34 patients (58.8%) had contralateral progression following surgery, whereas the mean follow-up duration of their cohort was long with 35.3 months (IQR, 18.1-100 months) [25]. Our previous studies have demonstrated that unilateral combined bypass surgery was associated with rapid radiological progression of contralateral vessels at short-term follow-up, resulting in rapid aggravation of main trunk stenosis and decreased cerebral blood ow on the non-OP side [11,13]. In the current study, we identi ed contralateral radiological progression in 11 pediatric patients (40.7%) within 3 to 6 months following unilateral combined bypass.…”
Section: Discussionmentioning
confidence: 99%
“…To address this issue, we have performed a series of study. Our previous study has demonstrated that rapid radiological progression of contralateral vessels at short-term follow-up after unilateral combined bypass surgery in pediatric MMD [13]. In this study, we aim to observe the progression pace on the non-OP side of pediatric MMD patients and explore its risk factors.…”
Section: Introductionmentioning
confidence: 97%
“…To examine the relationship between surgical treatment and MMD progression, Park et al conducted a retrospective study focusing on patients with pediatric MMD treated by indirect revascularization and found that 20 of 34 patients (58.8%) had contralateral progression following surgery, and the mean follow-up duration was long (35.3 months, IQR, 18.1–100 months) ( 26 ). Our previous studies have demonstrated that unilateral combined bypass surgery is associated with rapid radiological progression of contralateral vessels at short-term follow-up and can result in the rapid aggravation of main trunk stenosis and decreased cerebral blood flow on the non-OP side ( 11 , 13 ). In the current study, we identified contralateral radiological progression in 11 pediatric patients (40.7%) within 3 to 6 months following unilateral combined bypass surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A number of demographic and clinical variables, including age, sex, surgical side, angiographic findings, hemodynamic data, perioperative complications, and follow-up outcomes, were collected. Angiographic data including Suzuki stage, moyamoya vessel grade, and degree of neovascularization were evaluated independently by two neuroradiologists (Y Ma and X Lu), and any disagreement was settled by discussion with another neuroradiologist (B Yang) ( 13 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation